(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The scientific and practical issues of using land resources to enhance soil fertility are focused on the rational use of the soil layer, a crucial part of land resources, to maintain and increase its fertility. Increasing the fertility of cultivated soil in all aspects should remain a fundamental principle of agricultural development. Maintaining and enhancing the fertility of soils used in agricultural practices is directly linked to their proper and efficient use. From this perspective, instances of declining soil fertility due to improper use are also observed in some areas.